2001
DOI: 10.5194/we-2-32-2001
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of non-native Norway spruce plantation on abundance and species richness of ground beetles (Coleoptera: Carabidae)

Abstract: The impacts of non-native Norway spruce plantation on the abundance and species richness of carabids were studied in the B&uuml;kk National Park in Hungary, central Europe. Pitfall catches from recently established (5 yr old), young (15 yr after planting), middle-aged (30 yr after planting), old Norway spruce <i>Picea abies</i> plantation (50 yr after planting), and a native submontane beech forest (Fagetum sylvaticae) as a control stand were compared. <br><br> Our results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…The characteristic species is defined as the most characteristic species of each habitat type, found mostly in that habitat and present in the majority of sites belonging to that habitat. This proved to be a useful method to identify the characteristic invertebrate species in several habitats [4,22,23].…”
Section: Data Analysesmentioning
confidence: 99%
“…The characteristic species is defined as the most characteristic species of each habitat type, found mostly in that habitat and present in the majority of sites belonging to that habitat. This proved to be a useful method to identify the characteristic invertebrate species in several habitats [4,22,23].…”
Section: Data Analysesmentioning
confidence: 99%
“…In general, conifer plantations are considered low-diversity ecosystems (Peterken 1996;Cannell 1999) as compared to native mature forests (e.g. for carabid beetles: Fahy and Gormally 1998;Elek et al 2001;Magura et al 2002). However, the low structural heterogeneity of plantations can evolve due to the ageing process or management practices, progressively leading to a more diversified structure of the planted trees (Kint 2005), resembling that of natural deciduous forests, and, consequently, increasing variability of tree characteristics and the forest diversity (see Barbier et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Baguette and Gérard (1993) found that the species composition and richness of carabid communities in spruce plantations differed significantly among the studied age classes. On the contrary for Elek et al (2001), abundance and species richness did not present significative differences among spruce plantations of different ages.…”
Section: Discussionmentioning
confidence: 58%
“…The indicator value (IndVal) was applied to find characteristic species (Elek et al, 2001) and species assemblages characterising the "MF", "BE", "HO", "MP" and "PR" plantations. The novelty of this approach lies in the way it combines a species relative abundance to its relative frequency of occurrence in the groups of samples.…”
Section: Discussionmentioning
confidence: 99%